Strengthening the Value of Moderation and Quality of Adolescent Students at Madrasah Diniyah Al-Munfaq - Titin Widya Risni; Hendy Hendy; Adinda Khusnul Khotimah; Moh. Ali Maftu (Universitas Nurul Jadid, 2025)
Ngadiluwih District, Kediri Regency, has great potential in shaping a moderate and high-quality young generation, particularly within the environment of Madrasah Diniyah Al-Munfaq Badal. The social and cultural diversity of the local community, combined with its strategic geographical location, makes this area ideal for developing religious education that promotes the values of religious moderation. This program was designed to address social challenges such as intolerance and radicalism, which may emerge when religious understanding is not accompanied by a moderate and inclusive outlook. Students, as future leaders, play a crucial role in fostering a peaceful society and therefore need to be equipped with contextual and socially relevant religious values. The program utilized a dialogical and participatory approach through activities such as thematic discussions, religious moderation training, joint worship, inter-madrasah collaboration, community service, social visits, and reading clubs. Program results showed a 35% increase in students’ understanding of religious moderation, as reflected in pre- and post-test evaluations. Social skills also improved, indicated by active participation in inter-madrasah and community activities. Sustainable reading clubs and regular forums strengthened collaboration and inclusivity among students. This program demonstrates that religious education can effectively strengthen human values, tolerance, and social harmony in Indonesia’s diverse society.